Stress and Post-traumatic Growth of people with cancer: identification of associated factors - de Freitas Melo, Cynthia; Braga Teófilo, Marina; Huet Borges de Arruda, Gabriel; Kern de Castro, Elisa; Araújo de Morais, Normanda; Moreira Costa, Icaro (Psicooncología, 2024)
Objectives: Evaluate indicators and identify associated factors of post-traumatic stress disorder (PTSD) and post-traumatic growth (PTG) in individuals undergoing oncological treatment. Method: Quantitative, cross-sectional, analytical survey design with a non-probabilistic sample of 74 participants. Six instruments measuring PTSD, PTG, spiritual well-being, illness perception, and social support were employed. Data were analyzed using descriptive and inferential statistics in the Statistical Package for Social Science (SPSS). Results: It was evidenced that 21.60% of patients presented clinical indices of PTSD, and 85.12% showed a high index for PTG. High satisfaction indices were also observed for social support (86.48%), spiritual well-being (95.94%), and in identifying cancer as a potential threat to life (71.57%). Females, unmarried individuals, those inactive or unemployed, and those receiving public health support exhibited higher PTG indices. Women exhibit higher PTSD indices than men. Negative correlations were found between PTSD and spiritual well-being, and positive correlations with illness perception. Illness perception emerged as the variable with the greatest predictive power for PTSD indices. Conclusions: It is concluded that the threatening perception of the illness is a predictor of PTSD, highlighting it as a risk factor that requires attention in health prevention plans.
Keywords: Posttraumatic stress disorder; posttraumatic growth; cancer